Weight cycling and mortality among middle-aged and older women - Field, Alison E. (2009)
CONTEXT: Controversy exists around whether weight cycling increases morbidity and mortality. OBJECTIVE: To assess the independent association of weight cycling with mortality. DESIGN, SETTING, PARTICIPANTS: A prospective study of 44,876 middle-aged and older women in the Nurses' Health Study who provided information on intentional weight losses between 1972 and 1992, survived until at least 1994, had a body mass index ≥17 kg/m(2), and had no history of cancer (other than non-melanoma skin cancer) or heart disease. Women who reported they had intentionally lost ≥ 20 lbs at least 3 times were classified as severe weight cyclers. Women who had intentionally lost ≥ lbs at least 3 times, but did not meet the criteria for severe weight cycling, were classified as mild weight cyclers. MAIN OUTCOME MEASURES: All cause mortality. RESULTS: Between 1972 and 1992, approximately 18.8% of the women were mild weight cyclers and 8.0% were severe weight cyclers. During 12 years of follow-up 2,882 women died, of their deaths, 424 were due to cardiovascular events. Weight cyclers gained more weight during follow-up than non-cyclers (p <0.001). After adjusting for BMI at age 18, physical activity, smoking, post-menopausal hormone use, alcohol intake, net weight change from age 18, and change in physical activity, there was no increase in risk among mild (relative risk [RR]=0.84, 95% confidence interval [CI] 0.75–0.93) or severe cyclers (RR=0.90, 95% CI 0.77–1.04). Similar results were observed for cardiovascular mortality and among women 70 years of age or less. CONCLUSIONS: Repeated intentional weight losses were not predictive of greater all-cause or cardiovascular mortality.